Novel Cyclovirus Identified in Broiler Chickens With Transmissible Viral Proventriculitis in China - Yan, Tianxing; Li, Gen; Zhou, Defang; Yang, Xiaoxia; Hu, Liping; Cheng, Ziqiang (Frontiers in Veterinary Science, 2020)
In October 2018, an outbreak of transmissible viral proventriculitis (TVP) occurred in 30-day-old commercial broiler chickens on a farm in Weifang, China. TVP, an infectious viral disease characterized by runting and stunting, is associated with many viruses and has a significant economic impact on the global poultry industry. TVP is diagnosed according to clinical symptoms, gross and histological lesions, and negative PCR results for pathogenic bacteria, avian leukosis virus subgroup J, Marek’s disease virus, reticuloendotheliosis virus, infectious bursa disease virus, avian reovirus, chicken anemia virus, infectious bronchitis virus, chicken proventricular necrosis virus, gyrovirus 3 and chicken circovirus. To further detect the possible causative pathogens of TVP, we used PacBio third-generation sequencing to examine proventricular samples. A dominant abundance of the novel cyclovirus (CyCV), chCyCV-SDAU-1, was identified in broilers with TVP. The complete chCyCV-SDAU-1 genome was verified via inverse PCR, was 1936 bp long, and consisted of Rep, Cp and two intergenic regions. Phylogenetic tree analysis showed that chCyCV-SDAU-1 formed an independent branch with other cycloviruses. The homology of chCyCV-SDAU-1 with 20 others known cycloviruses was <40%. Retrospective investigation showed that the CyCV infection rate in the broilers with TVP was 80% (16/20), while no CyCV was found in healthy chickens. In conclusion, a novel CyCV was identified in chickens with TVP, though its role in this disease is unclear.